(untitled) - Carey, V. P. (Van P.) (Cambridge, UK,New York, 1999)
Many of the exciting new developments in microscale engineering are based on the application of traditional principles of statistical thermodynamics. This book offers a modern view of thermodynamics, interweaving classical and statistical thermodynamic principles and applying them to current engineering systems. It begins with coverage of microscale energy storage mechanisms from a quantum mechanics perspective and develops the fundamentals of classical and statistical thermodynamics. Next, applications of equilibrium statistical thermodynamics to solid, liquid, and gas phase systems are discussed. The remainder of the book discusses nonequilibrium thermodynamics of transport phenomena and introduces nonequilibrium effects and noncontinuum behaviour at the microscale. Although the text emphasizes mathematical development, it includes many examples and exercises illustrating how the theoretical concepts are applied to systems of scientific and engineering interest. It offers a fresh view of statistical thermodynamics for advanced undergraduate and graduate students as well as practitioners in mechanical, chemical, and materials engineering.
Vật lý thống kê
Keywords: Statistical thermodynamics,Thermodynamics,Nhiệt động học thống kê,Nhiệt động học